THE ROLE OF ISLAMIC HIGHER EDUCATION IN DEVELOPING THE CHARACTER AND ETHICS OF MUSLIM STUDENTS - Suhartini Suhartini; Muhamad Fajri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The purpose of this study is to explore the contribution of Islamic higher education in shaping the character and ethics of Muslim students. The findings of this study indicate that character education from an Islamic perspective is based on akhlaqul karimah, which emphasizes the importance of moral integrity, a sense of responsibility, and good personality. Islamic higher education has a long tradition in preserving and developing knowledge and spiritual values. Its strategic role is seen in the effort to incorporate Islamic values into the curriculum, through courses related to Islam such as tafsir, hadith, and Sufism ethics, as well as the development of a curriculum that combines revelation and reason. Values such as honesty, empathy, social responsibility, and justice are taught so that students become intellectually superior and also care about society with moral integrity. With a comprehensive approach that includes academic and non-academic activities, Islamic higher education has an important role in producing a generation of Muslims who are characterful, ethical, and ready to become agents of change in society